Sources of Forestry Information on the Internet - Sharma, Amrish K.; Deorani, S. C.; Gupta, Pawan K. (Indian Forester, 1997)
The Internet has revolutionised the computer and communications world like nothing before. The invention of the telegraph, telephone, radio and computer set the stage for this unprecedented integration of capabilities. The Internet is at once a world-wide broadcasting capability, a mechanism for information dissemination, and a medium for collaboration and interaction between individuals and their computers without any regard for geographic location. These databases contains textual, graphical, sound and movies (Multimedia) information.